Peculiarities of Interaction Deserosed Organ and the Parietal Peritoneum of the Implants with Porous NiTi (Experimental Study) - Vusik, A.N.; Dambaev, G.Ts.; Suhodolo, I.V.; Gunther, V.E.; Skidanenko, V.V.; Shvedova, M.V.; Latypov, V.R.; Kurtseitov, N.E.; Vusik, N.A.; Fimushkina, N.Yu. (KnE Materials Science, 2017)
The article’s abstract is no available.